PENGARUH MOTIVASI TERHADAP KINERJA PADA TENAGA KERJA DI STIKES X DI YOGYAKARTA - Ahmad, Aulia Ikhsan Gafar; Wibowo, Wisnu (LPPM Sekolah Tinggi Ilmu Kesehatan Yogyakarta, 2020)
ABSTARTCT Staff performance is so important for a new organization because it will help the orgaization to growing bigger and better organization. However, high staff performance is not an easy task because it would need a high motivation staff to show their best effort to finished their work. Therefore, the aim of this study is to examine the influence of motivation to staff performance of STIKes X. The method used in this research is quantitative method by using simple linear regression. Data was obtained from 33 respondents of STIKes X by using questionnare. The sampling technique used in this research is saturated samples. The result of this research shows that motivation has significant influence to staff performance (3,862 > 2,039 and 0,001 < 0,05) with coefficient of determination is 32,5%.